Allopurinol Disrupts Purine Metabolism to Increase Damage in Experimental Colitis - Corey S. Worledge; Rachael E. Kostelecky; Liheng Zhou; Geetha Bhagavatula; Sean P. Colgan; J. Scott Lee (Cells, 2024)
Inflammatory bowel disease (IBD) is marked by a state of chronic energy deficiency that limits gut tissue wound healing. This energy shortfall is partially due to microbiota dysbiosis, resulting in the loss of microbiota-derived metabolites, which the epithelium relies on for energy procurement. The role of microbiota-sourced purines, such as hypoxanthine, as substrates salvaged by the colonic epithelium for nucleotide biogenesis and energy balance, has recently been appreciated for homeostasis and wound healing. Allopurinol, a synthetic hypoxanthine isomer commonly prescribed to treat excess uric acid in the blood, inhibits the degradation of hypoxanthine by xanthine oxidase, but also inhibits purine salvage. Although the use of allopurinol is common, studies regarding how allopurinol influences the gastrointestinal tract during colitis are largely nonexistent. In this work, a series of in vitro and in vivo experiments were performed to dissect the relationship between allopurinol, allopurinol metabolites, and colonic epithelial metabolism and function in health and during disease. Of particular significance, the in vivo investigation identified that a therapeutically relevant allopurinol dose shifts adenylate and creatine metabolism, leading to AMPK dysregulation and disrupted proliferation to attenuate wound healing and increased tissue damage in murine experimental colitis. Collectively, these findings underscore the importance of purine salvage on cellular metabolism and gut health in the context of IBD and provide insight regarding the use of allopurinol in patients with IBD.